Leaching metals from saprolitic laterite ore using a ferric chloride solution. (20th January 2016) - Zhang, Peiyu; Guo, Qiang; Wei, Guangye; Meng, Long; Han, Linxin; Qu, Jingkui; Qi, Tao
Abstract: In this work, FeCl3 solution was used as a lixiviant to leach Ni, Co, Mg, and Mn from saprolitic laterite ore. Investigation into the leaching of these metals and the precipitation of Fe in the lixiviant, found the optimal leaching conditions to be a temperature of 150 °C, a Fe concentration in the lixiviant of 178.9 g/L, a liquid to solid ratio (L/S) of 1.0, and a leaching time of 90 min. The kinetics of the leaching process was also discussed. Saprolitic ore with and without goethite seeds was leached using FeCl3 solution under identical conditions. X-ray diffraction (XRD) analysis, infrared spectrometry (IR), and mineral liberation analysis (MLA) were used to characterize the leached residues. The leaching mechanism was analyzed based on these results. Highlights: Ferric chloride solution was used to leach saprolitic laterite. Ni and Co were leached selectively. Fe precipitated as FeOOH/Fe2 O3 and a manageable leaching solution was obtained. Mechanism of the leaching process was constructed.